Service Quality, Service Experience, and Customer Satisfaction: the Case of a Fitness Center in Breda, the Netherlands - Kamolrat, Potjanee; Laat, Tim de; Mitas, Ondrej; Rooij, Pieter de (Journal of Applied Economics and Management Strategy, 2019)
ABSTRACT This research aimed at investigating the influences of service quality and service experience on customer satisfaction in a fitness center business in Breda, the Netherlands. Primary data were gathered using online self-administered questionnaires distributed to members of the fitness center through Qualtrics. The majority of the respondents were Dutch (84%). Most of them were female (62%), and 67% of the respondents were university students in Breda. A five-point Likert scale was used to determine the agreement of each item of service quality, service experience, and satisfaction of customers. Multivariate multiple regression was used in order to analyze the influence of each service quality category, the psychological and atmospheric categories of the service experience, on customer satisfaction. The results showed that only some aspects of perceived service quality and service experience had significant influences on customer satisfaction. Furthermore, the findings showed that the gym staff, group lesson instructors, receptionists, sports hall coaches, and bar personnel had positive significant influences on overall satisfaction. Additionally, the customers suggested different needs for bringing about changes in the fitness center. Keywords: Service quality, service experience, customer satisfaction, fitness center, gym